The Protection of Traditional Knowledge in Peru: A Comparative Perspective - Susanna E. Clark; Isabel Lapeña; Manuel Ruiz (Washington University Global Studies Law Review, 2004)
This Article analyzes the policy and legal context for the protection of traditional knowledge, focusing on Peruvian Law 27811, Regime for the Protection of Indigenous Peoples’ Collective Knowledge Associated with Biodiversity (enacted on July 24, 2002) [Law 27811], as a case study.
Keywords: Biodiversity; Cultural property protection; Indigenous peoples; Traditional knowledge; International; Peru